PENGARUH BUDAYA ORGANISASI, KOMPETENSI, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PEGAWAI YANG DIMEDIASI OLEH MOTIVASI KERJA STUDI PADA DINAS PERTANIAN DAN KEHUTANAN KABUPATEN REMBANG (Jurnal Mahasiswa Pasca Sarjana, 2015)
The success of the performance of an organization is determined by the motivation to work because it can foster employee spirit weeks to work optimally in achieving organizational goals. In order to create synergies and foster employee motivation then indispensable factors are organizational culture, competencies and organizational commitment. The purpose of this study was to determine the effect of organizational culture, competencies, and organizational commitment to employee performance that is mediated by the motivation to work. The results of this study indicate that organizational culture is not significant and positive effect on employee performance, competency has a negative effect and no significant effect on employee performance, while organizational commitment and work motivation positive and significant impact on employee performance. Moreover, from the research shows that work motivation mediates the full effect of organizational culture on employee performance, motivation to work full mediating effect of competence on employee performance, and motivation not mediate the effect of organizational commitment on employee performance. Keywords : Organizational Culture, Competence, Organizational Commitment, Work Motivation and Employee Performance